(3Yde GLJeGY GdJfejIs - (3eMeO eMehO(B, (3GdLhgQjs ((3YeGf(B:s (3OGQ GdeSjQI(B,s, 2010)
(3GdHdGO GdfGejI aj GdYGde GdeYGUQ ,GdbVGjG GdGSGSjI dYde GdGLJeGY ,GdJZjjQ GdKbGaj h GdOjfGejI GdGLJeGYjI , GdYdGbI Hjf GdJZjjQ GdKbGaj h GdeLJeY , GdJfejI (B( (3GdJMOjK(B) (3Hjf cGQd eGQcS h eGcS ajHQ , GJLGg GdfeGPL Ch GdeDTQGJ , GdGJLGg GdJWhQj GdeMOK , GdGJLGg GdGfJTGQj , GdGJLGg GdSjchdhLj Ch GdSdhcj , GJLGg GdecGfI GdOhdjI h GdGJLGg GdeGQcSj GdLOjO h GNjQG GdeaGgje h GdCSGSjI aj OQGSI GdJfejIs
Keywords: (3GdJfejIs; (3Yde GLJeGY(B- (3GdJfejIs; (3Yde GdELJeGYs